(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Sustainability reporting has become a topical issue in recent years as it is no longer enough to make claims about the sustainability level of companies, but it is also necessary to demonstrate their sustainability efforts. For this purpose, sustainability reporting has grown from a voluntary basis into a legal obligation for some organizations, which speaks in favor of the importance of sustainable business globally. This paper aims to provide a wider perspective and theoretical support for research on sustainability reporting. A literature review of 52 papers from the Web of Science database indicates the following eight aspects as a trend in the literature reviews of sustainability reporting: Assurance, Boards, Communication, Framework, Impact, Indicators, Materiality and Practices. The paper highlights problems and provides challenges related to sustainability reporting and research opportunities for exploring sustainability reporting in future studies.